Inflammatory myofibroblastic tumor presenting as paraneoplastic pemphigus in a 7-year-old girl. (2016)
Paraneoplastic pemphigus is an autoimmune disease associated with an underlying tumor. Several cases have been reported as unusual pemphigus vulgaris, erythema multiforme, or paraneoplastic bullous disease,1 but the incidence of the condition is unknown.2 Response to treatment is generally poor, with significant morbidity and mortality. This condition is clinically characterized by severe mucositis and polymorphic blistering skin eruptions, and histologically by acantholysis, keratinocyte necrosis, and interface dermatitis.3 Immunoprecipitation and immunoblot testing detect autoantibodies against desmosomal polypeptides.4 We describe a case of paraneoplastic pemphigus associated with an abdominal inflammatory myofibroblastic tumor in a 7-year-old girl.